Faktor-Faktor yang Memengaruhi Sikap Afektif Petani pada Indeks Pertanaman (IP) Padi 400 di Kecamatan Ngemplak Kabupaten Boyolali - Prisca Puspita Sari; Suminah Suminah; Putri Permatasari (Universitas Sebelas Maret, 2023)
The Rice Cropping Index 400 (IP Padi 400) is one of the government’s initiatives to boost the production of rice commodities. The goal of the IP Padi 400 is to maximize the cropping index while optimizing the spatial and temporal patterns of rice cultivation. The aims of this study are to (1) know the variables influencing farmers’ affective attitudes toward the IP Padi 400 and (2) determine the effect of factors that influence affective attitudes on the farmers’ affective attitudes toward the IP Padi 400 in Ngemplak Sub-district, Boyolali Regency. This study used quantitative methods. A sample consisting of 47 participants was gathered by the census method. The analysis used multiple linear regression. The results of this study are: (1) non-formal education variables have a low influence; however, government support from the Ministry of Agriculture of Indonesia and agricultural extensions have a very significant influence and (2) non-formal education variables, government support, and agricultural extensions have significant influence on the formation of farmers’ attitudes toward the IP Padi 400.